2015
DOI: 10.3341/jkos.2015.56.9.1392
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dynamic Contour Tonometry and Goldmann Applanation Tonometry in Relation to Central Corneal Thickness

Abstract: Purpose: In this study we compared the intraocular pressures (IOPs) measured using dynamic contour tonometry (DCT) and Goldmann applanation tonometry (GAT) and investigated the correlation between central corneal thickness (CCT) and IOP. Methods: In a prospective study, 178 eyes of 91 subjects with glaucoma and glaucoma suspect were enrolled. IOP was measured using DCT and GAT and CCT was measured using ultrasound pachymetry. Each eye was classified into 1 of 3 groups according to their CCT: low CCT (Group A; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Tear film instability can lead to fluctuations in IOP measurements due to changes in tear volume and composition. Several studies have reported that tear film instability can affect the accuracy of IOP measurements obtained using GAT, the most commonly used method for measuring IOP [4,5]. However, the effects of tear film can be avoided by dynamic contour tonometry, rebound tonometer, noncontact tonometry [6,7].…”
Section: Keratitis-related Conditions Affecting the Iop Measurementmentioning
confidence: 99%
“…Tear film instability can lead to fluctuations in IOP measurements due to changes in tear volume and composition. Several studies have reported that tear film instability can affect the accuracy of IOP measurements obtained using GAT, the most commonly used method for measuring IOP [4,5]. However, the effects of tear film can be avoided by dynamic contour tonometry, rebound tonometer, noncontact tonometry [6,7].…”
Section: Keratitis-related Conditions Affecting the Iop Measurementmentioning
confidence: 99%